Fifth Grade Students‘ Problem Solving Ability of Flood Disaster - Anisa Listiani; M. Jaya Adi Putra; Mahmud Alpusari (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
The research is aimed to identify and describe the ability of fifth grade students in solving problems of disaster mitigation. This study was implemented in a public elementary school in Kampar, Riau, Indonesia in 2019. The type of research was qualitative research. The subject of this study was 42 fifth grade students. Instruments were arranged to refer to problem-solving indicators. After the instruments were validated by experts and tested by students, it was then used to retrieve data. The data is categorized and grouped according to the device already created. Based on the results of the study it showed that the students ' ability has been in an excellent category in carrying out problems and examining problems, while their ability was a poor category in planning, implementing, and evaluating the solutions that have been made.